Arthroscopy of the Elbow in Dogs - Bardet, J. F. (Veterinary and Comparative Orthopaedics and Traumatology, 1997)
The craniolateral portal of the elbow is described. The technique was applied and evaluated in 34 dogs (38 elbows). A detailed description and classification of the fragmented coronoid process (FCP) is given. All patients with FCP were treated successfully using a second craniomedial portal. Complications were not observed. The technique appears to be safe and reliable and could also be used for other procedures such as removal of loose bodies, treatment of osteochondritis dissecans of the medial condyle, reduction of selective humeral condylar fractures, excision of osteophytes and other diagnostic purposes. It also eliminates the need for exploratory arthrotomies of the elbow joint in dogs.The cranial portals of the 38 elbows in 34 dogs allowed proper evaluation and treatment of the lesions of the medial coronoid process. A classification in 7 types of lesions of the medial coronoid process was established. All dogs were treated successfully by either removal of the FCP or by a proximal ulnar sliding osteotomy.
Keywords: Arthroscopy; elbow joint; dog; coronoid process